2020
DOI: 10.1039/d0bm01427c
|View full text |Cite
|
Sign up to set email alerts
|

Fe-TCPP@CS nanoparticles as photodynamic and photothermal agents for efficient antimicrobial therapy

Abstract: Traditional antibacterial therapies always rely on antibiotics, which have led to the overuse of antibiotics and caused the emergence of multidrug-resistant (MDR) bacteria in recent years. In this study, an...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
40
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(41 citation statements)
references
References 44 publications
1
40
0
Order By: Relevance
“…The antibacterial performance of MOF‐545 were also compared with that of other TCPP‐containing materials against E. coli (Table S2). MOF‐545 exposed to white LED light (4 mW/cm 2 ) for 20 min can reduce the number of E. coli colonies by 3 log while other TCPP‐containing materials required higher power intensity or longer irradiation time [6d,f,26] . In addition, The MOFs exhibited better photodynamic antibacterial performance for S. aureus than E. coli under the same experimental conditions due to the different cell wall structures of Gram‐negative and Gram‐positive bacteria [5] .…”
Section: Resultsmentioning
confidence: 99%
“…The antibacterial performance of MOF‐545 were also compared with that of other TCPP‐containing materials against E. coli (Table S2). MOF‐545 exposed to white LED light (4 mW/cm 2 ) for 20 min can reduce the number of E. coli colonies by 3 log while other TCPP‐containing materials required higher power intensity or longer irradiation time [6d,f,26] . In addition, The MOFs exhibited better photodynamic antibacterial performance for S. aureus than E. coli under the same experimental conditions due to the different cell wall structures of Gram‐negative and Gram‐positive bacteria [5] .…”
Section: Resultsmentioning
confidence: 99%
“…ROS causes random oxidation of DNA, RNA, and/or lipid, leading to bacterial destruction, and thus preventing the development of specific resistance mechanisms in bacteria. 295,297…”
Section: Applications Of Gqd-pp/pc Conjugatesmentioning
confidence: 99%
“…ROS causes random oxidation of DNA, RNA, and/or lipid, leading to bacterial destruction, and thus preventing the development of specific resistance mechanisms in bacteria. 295,297 Sen et al recently reported the antibacterial activity of novel ZnPcs (3,4)-containing octa-imines and their nanoconjugates (3@N,S-GQDs and 4@N,S-GQDs) in S. aureus. As the singlet oxygen production increased for 3@N,S-GQDs and 4@N, S-GQDs compared to ZnPcs (3,4) alone, photoactivity resulted in complete cell destruction.…”
Section: Biomaterials Science Reviewmentioning
confidence: 99%
“…18). The authors showed that the introduction of metal nodes prevented the self-aggregation of the porphyrin and improved 1 O 2 generation [117] . By using both PTT and PDT, the authors reached a 98% of E. coli reduction of bacterial survival, while PTT or PDT only reached 45% and 42%, respectively.…”
Section: Magnetic Nanoparticlesmentioning
confidence: 99%